Evacuation and human behaviours in tunnel fires - Frantzich, Håkan (Proceedings from the 11th International Symposium on Tunnel Safety and Security, 2025)
Tunnel evacuation is a challenge that requires a well-prepared strategy and relevant technical and organizational measures to be successful. The article focuses on the relation between knowledge about human behaviour during an evacuation process and how this knowledge is obtained through investigations after fires and through well-planned experiments. Furthermore, theories are introduced that explain and describe human behaviour in different situations, such as Canter's behavioural sequences, Sime's affiliation theory and the understanding of social influences within a group of individuals. A timeline model is presented that connects the behavioural description of how people in general act during fires with an engineering model that can be used for design. In addition, results from some experiments are presented where the effectiveness of different technical installations during an evacuation process has been investigated.